Chondrochelia Guţu, 2016 (Crustacea, Peracarida, Tanaidacea, Leptocheliidae) from North America: new species, redescription and distribution using morphological and molecular data - Jani Jarquín-González; Luis F. Carrera-Parra (PeerJ, 2022)
Until now, four species of the genus Chondrochelia Guţu, 2016 have been recorded from America. Using morphological and molecular data, we were able to recognize and describe two new species, Chondrochelia caribensis sp. nov. from the Mexican Caribbean and Chondrochelia winfieldi sp. nov. from the Gulf of Mexico. We found significant genetic divergence values between species based on the nucleotide sequences of cytochrome oxidase subunit I to support the morphological data. Also, the range of distribution of two species: Chondrochelia mexicana (Jarquín-González, García-Madrigal & Carrera-Parra, 2015) and Chondrochelia ortizi (Jarquín-González, 2016), were expanded within their described geographic regions. In contrast, the supposed distribution of the Brazilian C. dubia in the Mexican Caribbean and the Gulf of Mexico was rejected. Additionally, Chondrochelia algicola (Harger, 1878) was redescribed based upon type material. Minute details and ornamentation of some structures of three species were examined using SEM.